Perkembangan Keterampilan Sosial Anak dalam Keluarga Single Parent - Azka, Milatul; Shanie, Arsan; Abdillah, Nisa Ricma; Alawiyah, Alya; Sayifullah, M. Faridh; Ainurrohima, Afina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of social skills is crucial for children’s overall well-being, yet children in single-parent families often face unique challenges that may impede this development. This study aims to comprehensively analyze the social skill development of children in single-parent households by reviewing national and international literature from 2015 to 2025. The systematic literature review reveals that children in single-parent families are at higher risk for social, emotional, and academic difficulties, with reported rates of strained peer interactions (76%) and frequent emotional distress (78.5%). However, adaptive parenting styles, strong social support, and tailored interventions, including Parent Management Training (PMT) and school-based programs, emerge as significant protective factors. Furthermore, children’s involvement in household chores is positively associated with increased social skills and fewer depressive symptoms. The findings underscore the importance of holistic, strength-based interventions that address both the challenges and inherent resilience within single-parent families to foster optimal social skill development